2019
DOI: 10.1080/07853890.2019.1596302
|View full text |Cite
|
Sign up to set email alerts
|

Extensive phenotype data and machine learning in prediction of mortality in acute coronary syndrome – the MADDEC study

Abstract: Objective: Investigation of the clinical potential of extensive phenotype data and machine learning (ML) in the prediction of mortality in acute coronary syndrome (ACS). Methods: The value of ML and extensive clinical data was analyzed in a retrospective registry study of 9066 consecutive ACS patients (January 2007 to October 2017). Main outcome was sixmonth mortality. Prediction models were developed using two ML methods, logistic regression and extreme gradient boosting (xgboost). The models were fitted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 29 publications
0
39
1
Order By: Relevance
“…ML has been shown to achieve the same or better prognostic definition in several clinical conditions, as compared to conventional statistical methods. In particular, ML can better predict clinical deterioration in the ward [ 26 ], mortality in acute coronary syndrome [ 27 ], survival in patients with epithelial ovarian cancer [ 28 ], complications of bariatric surgery [ 29 ], and risk of metabolic syndrome [ 30 ]. On the other hand, other studies reported that ML and conventional statistical methods have similar prognostic usefulness in predicting mortality in intensive care units [ 31 ], readmission in patients hospitalized for heart failure [ 32 ], and all-cause mortality and cardiovascular events [ 33 ].…”
Section: Applications Of ML In Medicinementioning
confidence: 99%
“…ML has been shown to achieve the same or better prognostic definition in several clinical conditions, as compared to conventional statistical methods. In particular, ML can better predict clinical deterioration in the ward [ 26 ], mortality in acute coronary syndrome [ 27 ], survival in patients with epithelial ovarian cancer [ 28 ], complications of bariatric surgery [ 29 ], and risk of metabolic syndrome [ 30 ]. On the other hand, other studies reported that ML and conventional statistical methods have similar prognostic usefulness in predicting mortality in intensive care units [ 31 ], readmission in patients hospitalized for heart failure [ 32 ], and all-cause mortality and cardiovascular events [ 33 ].…”
Section: Applications Of ML In Medicinementioning
confidence: 99%
“…In MADDEC, conventional electronic health record (EHR) data are combined with clinical cardiovascular phenotype data collected by treating physicians into a dedicated KARDIO registry. The register contains high-quality phenotype data for risk prediction, with added information over generic hospital EHRs, such as detailed information on patients' hospitalizations, invasive and non-invasive procedures, as well as outpatient visits [20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…Before training, the synthetic minority oversampling technique was adopted to deal with the unbalanced issue of the training data set [34]. XGBoost (Extreme Gradient Boosting), an ensemble tree-based model, has been shown to be more likely to achieve better model performance and to be more interpretable than other ML models, such as logistic regression or support vector machine [35][36][37][38][39]. Therefore, we choose the XGBoost algorithm to develop the prediction model for each outcome.…”
Section: Model Buildingmentioning
confidence: 99%